Islamic Branding, Word of Mouth, dan Harga terhadap Customer Loyalty Buya di Kudus (Jurnal Ekonomi dan Bisnis Islam, 2024)
AbstractThis study aims to determine the influence of Islamic branding, word of mouth, and price on Buya's customer loyalty in Kudus. This type of research is field research with a quantitative approach with questionnaires as research instruments. Determination of samples using accidental sampling method as many as 96 respondents. Instrument testing using validity, reliability tests, classical assumption testing, hypothesis testing using multiple linear regression tests, Coefficient of Determination (R2), t-test, and f-test with the help of IBM SPSS 25 data processing program. This study shows the result that the Islamic branding variable has no significant effect on loyalty customers obtained from the value of tcount<ttable and sig>0.05 with the acquisition of a value 0.495<1,986 and sig value 0.622. Word of mouth variable has a significant effect on loyalty customers obtained from the value of tcount>ttable and sig<0,05 with the acquisition of a value 10,257>1,986 and sig value 0,000. The price variable has a significant effect on loyalty customers with the acquisition of a value of 3,722>1,986 and a sig value of 0,000. The research results show that Islamic branding does not have a significant effect on customer loyalty, while word of mouth and price have a positive and significant effect on customer loyalty for Buya products in Kudus.Keywords: Islamic Branding; Word of Mouth; Price; Customer Loyalty. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh Islamic branding, word of mouth, dan harga terhadap customer loyalty Buya di Kudus. Jenis penelitian ini ialah field research menggunakan pendekatan kuantitatif dengan kuesioner sebagai instrumen penelitian. Penentuan sampel menggunakan metode accidental sampling sebanyak 96 responden. Pengujian instrumen menggunakan uji validitas, reliabilitas, pengujian asumsi klasik, pengujian hipotesis menggunakan uji regresi linier berganda, Koefisien Determinasi (R2), uji-t, dan uji-f dengan bantuan program olah data IBM SPSS 25. Penelitian ini menunjukkan hasil bahwa variabel Islamic branding tidak berpengaruh secara signifikan terhadap customer loyalty diperoleh dari nilai thitung<ttabel dan sig>0,05 dengan perolehan nilai 0,495<1,986 dan nilai Sig. sebesar 0,622. Variabel word of mouth berpengaruh positif dan signifikan terhadap customer loyalty diperoleh dari nilai thitung>ttabel dan sig<0,05 dengan perolehan nilai 10,257>1,986 dan nilai Sig. sebesar 0,000. Variabel harga berpengaruh positif dan signifikan terhadap customer loyalty dengan perolehan nilai 3,722>1,986 dan nilai Sig. 0,000. Hasil penelitian diperoleh bahwa Islamic branding tidak berpengaruh secara signifikan terhadap customer loyalty, sedangkan word of mouth dan harga berpengaruh positif dan signifikan terhadap customer loyalty produk Buya di Kudus.Kata Kunci: Islamic Branding; Word of Mouth; Harga; Customer Loyalty.